Immune‐checkpoint inhibitor‐associated diabetes compared to other diabetes types ‐ A prospective, matched control study. Issue 12 (29th July 2021) - Tittel, Sascha R.; Laubner, Katharina; Schmid, Sebastian M.; Kress, Stefan; Merger, Sigrun; Karges, Wolfram; Wosch, Frank J.; Altmeier, Marcus; Pavel, Marianne; Holl, Reinhard W.; ,
Abstract: Background: To describe checkpoint inhibitor‐induced diabetes mellitus (CPI‐DM) and to compare with regular type 1 (T1DM), type 2 (T2DM), and medication‐induced diabetes mellitus (MI‐DM). Methods: We included 88 177 adult patients from the Diabetes Patient Follow‐Up (DPV) registry with diabetes manifestation between 2011 and 2020. Inclusion criteria were T1DM, T2DM, MI‐DM, or CPI‐DM. Because of the heterogeneity between the groups, we matched patients by age, sex, and diabetes duration using propensity scores. Patient data were aggregated in the respective first documented treatment year. Results: The matched cohort consisted of 24 164 patients; T1DM: 29, T2DM: 24000, MI‐DM: 120, CPI‐DM: 15 patients. Median age at manifestation of CPI‐DM patients was 63.6 (57.2‐72.8) years (53.3% male). Body mass index in CPI‐DM patients was significantly lower (26.8 [23.9‐28.1] kg/m 2 ) compared with T2DM patients (29.8 [26.2‐34.3] kg/m 2, P = 0.02). At manifestation, HbA1c was significantly higher in CPI‐DM compared with MI‐DM, but there was no difference during follow‐up. Diabetic ketoacidosis (DKA) was documented in six CPI‐DM patients (T1DM: 0%, T2DM: 0.4%, MI‐DM: 0.0%). Fourteen CPI‐DM patients were treated with insulin, and three received additional oral antidiabetics. The most common therapy in T2DM was lifestyle modification (38.8%), insulin in MI‐DM (52.5%). Concomitant autoimmune thyroid disease was present in four CPI‐DM patients (T1DM: 0.0%, T2DM: 1.0%, MI‐DM: 0.8%). Conclusions: The data from this controlled study show that CPI‐DM is characterized by a high prevalence of DKA, autoimmune comorbidity, and metabolic decompensation at onset. Structured diagnostic monitoring is warranted to prevent DKA and other acute endocrine complications in CPI‐treated patients. Abstract : Highlights This prospective study compares 15 patients with immune‐checkpoint induced diabetes mellitus (CPI‐DM) with a propensity score matched cohort of patients with other diabetes types. Diabetic ketoacidosis at onset and autoimmune comorbidity is more frequent in CPI‐DM patients. This can be avoided by regular glucose measurements and education on hyperglycemia. 摘要: 背景: 了解检查点抑制剂诱导的糖尿病(CPI‐DM)与普通1型糖尿病(T1 DM)、2型糖尿病(T2 DM)和药物诱导的糖尿病(MI‐DM)的异同。 方法: 我们纳入了2011年至2020年间来自糖尿病患者随访(DPV)登记处的88177名有糖尿病表现的成年患者。纳入标准为T1 DM、T2 DM、MI‐DM或CPI‐DM。由于两组之间的异质性, 我们使用倾向性评分将患者按年龄、性别和糖尿病病程进行配对。患者数据在各自记录在案的第一个治疗年度汇总。 结果: 匹配队列为24164例, 其中T1 DM 29例, T2 DM 24000例, MI‐DM 120例, CPI‐DM 15例。CPI‐DM患者发病年龄中位数为63.6岁(57.2 72.8岁)(男性53.3%)。CPI‐DM组体重指数(26.8[23.9 28.1]kg/m 2 )明显低于T2 DM组(29.8[26.2 34.3]kg/m 2, P=0.02)。CPI‐DM组糖化血红蛋白(HbA1c)明显高于MI‐DM组, 但随访时差异无统计学意义(P>0.05)。在6例CPI‐DM患者中发现糖尿病酮症酸中毒(DKA), 其中T1 DM:0%, T2 DM:0.4%, MI‐DM:0.0%。14名CPI‐DM患者接受胰岛素治疗, 3名患者接受额外的口服抗糖尿病药物治疗。T2 DM患者最常见的治疗方法是生活方式改变(38.8%), MI‐DM患者最常见的治疗方法是胰岛素(52.5%)。4例CPI‐DM患者合并自身免疫性甲状腺疾病(T1 DM:0.0%, T2 DM:1.0%, MIDM:0.8%)。 结论: 这项对照研究的数据显示, CPI‐DM的特点是DKA患病率高、自身免疫性疾病以及代谢紊乱。对于接受CPI治疗的患者, 有必要进行结构化的诊断监测, 以预防DKA和其他急性内分泌并发症。